Efficient Radiation Pattern Estimation of Slot Array Antennas Covered With Frequency Selective Surfaces Using Deterministic Ray Tracing - Daeyeong Yoon; Jihyung Kim; Hokeun Shin; Dong-Yeop Na; Yong Bae Park (IEEE Access, 2023)
In this paper, we propose a novel algorithm to compute the radiation pattern of a slot array antenna covered with frequency selective surfaces (FSS) based on ray tracing technique. We observe that the proposed algorithm can greatly reduce computational resources while yielding accurate numerical solutions, compared to cases using standard full-wave and conventional high-frequency approaches. The underlying principle is to combine the image method and physical optics technique. More specifically, the proposed algorithm (i) employs a boundary box that encloses the slot array antenna with FSS to correct phase errors and then (ii) calculates equivalent surface currents flowing on the boundary box. The surface of the boundary box is discretized by regular grids (or boundary meshes) and a ray path reaching each square cell in the boundary meshes is determined based on the image method. After collecting all the rays hitting the boundary meshes, equivalent surface current densities can be computed for the resulting radiation pattern. The proposed algorithm is suited best for dealing with electrically large structures much more efficiently and can advance the existing design process.